Dynamics of apokamp-type atmospheric pressure plasma jets initiated in air by a repetitive pulsed discharge; Physics of Plasmas; Vol. 24, iss. 4 - Tarasenko V. F. Victor Fedotovich; Sosnin E. A. Eduard Anatoljevich; Skakun V. S. Viktor Semenovich; Panarin V. A. Viktor Aleksandrovich; Trigub M. V. Maksim Viktorovich; Evtushenko G. S. Gennady Sergeevich (2017, 2017)
Title screen